Association between α‐glucosidase inhibitor use and psoriatic disease risk in patients with type 2 diabetes mellitus: A population‐based cohort study. Issue 11 (16th September 2021) - Huang, Pei‐Ju; Wei, James Cheng‐Chung; Liu, Yen‐Tze; Lin, Ching‐Heng; Lin, Chi‐Chien; Chen, Hsin‐Hua
Abstract: Aims: To investigate the association between the use of alpha‐glucosidase inhibitors (AGIs) and the risk of psoriatic disease (ie, psoriasis and psoriatic arthritis) in patients with type 2 diabetes mellitus (T2DM) treated with metformin. Methods: Using the 1999‐2013 Taiwanese Longitudinal Cohort of Diabetes Patients Database, we identified patients with T2DM who initiated hypoglycaemic treatment between 2003 and 2012. After excluding patients with a history of psoriatic disease ( International Classification of Disease, Ninth Revision, Clinical Modification codes 696.0‐1) before T2DM diagnosis, patients who received antidiabetic treatment for <90 days, and patients aged <20 or >100 years, we identified 1390 patients who received metformin+AGIs (AGI exposure group) and 47 514 patients who received metformin only (comparison group). We matched the two groups at a 1:10 ratio by age, sex, and index date of T2DM drug use. The association between AGI use and psoriatic disease risk was analysed using a Cox proportional hazard mode; time‐dependent covariates for factors were reported in terms of hazard ratios (HRs) with 95% confidence intervals (CIs) after age, sex, T2DM duration, and comorbidities were controlled for. Results: After adjusting the AGI exposure and comparison groups for potential confounders, we found that psoriatic disease risk was associated with metformin+AGI use when AGI was discontinued for 30 days (HR, 8.77; 95% CI, 1.58‐48.5) and when a high AGI dose was administered; furthermore, the risk declined during AGI discontinuation. Conclusions: This population‐based study reports that AGI use and interruption of AGI use may be associated with increased psoriatic disease risk in treated patients with T2DM.